FELDA IFFCO / Ahmad Tarmizi Sazali ... [et al.] - Sazali, Ahmad Tarmizi; Abu Zahar, Muhammad Zaim; Samiran, Noor Shahira; Jeffery, Nur Shafira (2019)
According to Corley (2009), palm oil is an important source of edible oil, and also a potential biofuel raw material. In the sometimes heated debate over the expansion of the oil palm industry, the distinction between these uses is rarely made. Future demand for edible oil can be estimated from population projections and per capita consumption. The whole community needs palm oil to meet daily needs. FELDA IFFCO integrates the entire value chain from oil palm cultivation, milling, refining, processing, branding and distribution of a complete range of palm and palm kernel based oils and fats to global markets. FELDA IFFCO not only produces and markets a wide range of products that cater to the daily needs of households across the world, but also manufactures derivatives and intermediates for baking, food and non-food uses as well.